2004
DOI: 10.4049/jimmunol.172.6.3883
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Recognition of Desmoglein 3 Peptides in Patients with Pemphigus Vulgaris and Healthy Individuals

Abstract: Pemphigus vulgaris is a severe autoimmune disease caused by autoantibodies against the cutaneous adhesion molecule, desmoglein 3 (Dsg3). The aim of this study was to characterize the specificity of autoreactive Th cells, which presumably regulate Dsg3-specific autoantibody production. Ninety-seven Th1 and Th2 clones isolated from 16 pemphigus patients and 12 HLA-matched healthy donors recognized the Dsg3 peptides, DG3(78-94), DG3(96-112), DG3(189-205), DG3(205-221), and DG3(250-266). Peptide DG3(96-112), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
104
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 45 publications
13
104
0
5
Order By: Relevance
“…Involvement of Th cells in the pathogenesis of PV has been suggested by several studies: both Dsg3-reactive Th1 and Th2 cells were identified by our group and others (11,12) and appear to recognize epitopes of the extracellular domain of Dsg3 (13). A critical role for autoreactive T cells in the induction and regulation of Dsg3 autoantibody production has been suggested in a recent study by Nishifuji et al (14).…”
Section: Inhibition Of the Transcription Factor Foxp3 Converts Desmogsupporting
confidence: 54%
See 1 more Smart Citation
“…Involvement of Th cells in the pathogenesis of PV has been suggested by several studies: both Dsg3-reactive Th1 and Th2 cells were identified by our group and others (11,12) and appear to recognize epitopes of the extracellular domain of Dsg3 (13). A critical role for autoreactive T cells in the induction and regulation of Dsg3 autoantibody production has been suggested in a recent study by Nishifuji et al (14).…”
Section: Inhibition Of the Transcription Factor Foxp3 Converts Desmogsupporting
confidence: 54%
“…The recombinant protein PVhis, a fusion protein consisting of the entire extracellular domain of Dsg3 linked to an E-tag and histidine-tag, was used as a source of human Dsg3 and expressed in a baculovirus system with SF21 insect cells as described previously (12,13). For the production of Dsg3 protein, 3 ϫ 10 8 High-Five insect cells were inoculated with PVhis baculovirus at a multiplicity of infection of 10.…”
Section: Production and Purification Of Human Recombinant Dsg3mentioning
confidence: 99%
“…Both Dsg3-reactive Th1 and Th2 cells were identified by our group and others (4, reviewed in Ref. 5) and appear to recognize epitopes of the extracellular domain of Dsg3 in association with HLA-DRB1*0402 and HLA-DQB1*0503 (6). A critical role for autoreactive T cells in the induction and regulation of Dsg3 autoantibody production has been suggested by a recent study by Nishifuji et al (reviewed in Ref.…”
mentioning
confidence: 71%
“…Active immune regulation may thus be operative in Dsg3-responsive healthy individuals. It is presumed that this is not the consequence of deletion or immune deviation of autoreactive T cells because autoreactive Th cells specific for identical Dsg3 epitopes were detected both in patients and healthy donors (6).…”
mentioning
confidence: 99%
“…Noteworthy, recent studies in pemphigus vulgaris, an unrelated autoimmune bullous skin disorder, showed that autoaggressive T cells specific for desmoglein 3 preferentially targeted regions located in the NH 2 -terminal domains EC1 and EC2 (38) that were also preferentially recognized by IgG autoantibodies (39). In a HLA class II-transgenic mouse model of myasthenia gravis, autoreactive T cells responded to three cytoplasmic peptide sequences of the human acetylcholine receptor, which were also targeted by the pathogenic autoantibodies (40).…”
Section: Discussionmentioning
confidence: 99%